Sobre la font d’una font del «Tirant lo Blanch» i la modernitat de la novel·la - Butinyà i Jiménez, Júlia (Caplletra. Revista Internacional de Filologia, 1997)
Throughout time mankind has resigned himself to the changeability of Fortune. Each cultural expression has approached this topic from a different paint of view. On the basis of the comparison between the concepts of Fortune in Petrarca, Metge and Martorell, the author analyses the progressive modernity which arises at the end of the Middle Ages in both the literary and the ethical fields. Júlia Butinyà reviews the different episodes of the Tirant lo Blanch, and Petrarca’s De Remediis and Metge’s Lo somni which confirm the different stages on the concept of Fortune. If Petrarca proposes to rationally control passions in order to counteract the actions of Fortune, Metge contradicts him and exposes the bad predictions expressed in Tirant lo Blanch: Fortune does not respect these who are virtuous either.